Functional traits predict drought performance and distribution of Mediterranean woody species (Acta Oecologica, 2014)
Water availability is one of the key environmental factors that affect plant establishment and distribution. In many regions water availability will decline with climate change, exposing small seedlings to a greater likelihood of drought. In this study, 17 leaves, stem, root, and whole-plant traits of ten woody Mediterranean species were measured under favourable growing conditions and seedling drought survival was evaluated during a simulated dry-down episode. The aims of this study were: i) to assess drought survival of different species, ii) to analyse which functional traits predict drought survival time, and iii) to explain species distribution in the field, based on species drought survival and drought strategies. Drought survival time varied ten-fold across species, from 19 to 192 days. Across species, drought survival was positively related to the rooting depth per leaf area, i.e., the ability to acquire water from deeper soil layers while reducing transpiring leaf area. Drought survival time was negatively related to species ability to grow quickly, as indicated by high relative growth and net assimilation rates. Drought survival also explained species distribution in the field. It was found that species were sorted along a continuum, ranging between two contrasting species functional extremes based on functional traits and drought performance. One extreme consisted of acquisitive fast-growing deciduous species, with thin, soft metabolically active leaves, with high resource use and vulnerability to drought. The opposite extreme consisted of conservative slow-growing evergreen species with sclerophyllous leaves, deep roots, a low transpiring area, and low water use, resulting in high drought survival and drought tolerance. The results show that these drought strategies shape species distribution in this Mediterranean area.